Denotative and Connotative Meanings in the Religious Song “Angel” by Libera: A Semantic Perspective - Angel Lamtama Sihaloho; Bernike Anggita Ristia Damanik (JURNAL ILMIAH NUSANTARA, 2026)
This study explores the song Angel by Libera through a semantic perspective. The main aim of this research is to identify and explain the denotative and connotative meanings found in the lyrics. Semantics is used as the main theory to understand how meaning is formed in language, especially in song lyrics. The data used in this study come from the lyrics of the song Angel. The analysis shows that the lyrics contain both literal meanings (denotative) and implied meanings (connotative). The denotative meanings refer to words like angel, light, voice, and wings in their direct sense, while the connotative meanings reflect deeper ideas such as protection, hope, spiritual guidance, peace, and emotional comfort. The findings indicate that the song does not only communicate simple messages through words, but also conveys emotional and spiritual meanings that can be interpreted in different ways by listeners. Therefore, semantic analysis helps uncover the hidden meanings behind the lyrics and shows how language is used to express human feelings and spiritual values.